2017
DOI: 10.1093/gerona/glx210
|View full text |Cite
|
Sign up to set email alerts
|

Mental Fatigue Increases Gait Variability During Dual-task Walking in Old Adults

Abstract: Data indicate that mental fatigue, induced by sustained cognitive activity, can impair gait performance during dual-task walking in old adults. The susceptibility to mental fatigue could be a new intrinsic risk factor for falls in older people and should be taken into account when dual-task gait analyses are performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 23 publications
4
55
1
Order By: Relevance
“…It has been shown that state fatigue induced by sustained cognitive activity can be detrimental to subsequent endurance performance (Marcora et al, 2009). Therefore, state fatigue was quantified before each testing session using the fatigue scale of the Profile of Mood States (POMS-F) (Behrens et al, 2018). The POMS-F has been shown to provide a reliable and valid instrument to assess the level of state fatigue across a wide range of cohorts (O'Connor, 2004).…”
Section: State Fatiguementioning
confidence: 99%
“…It has been shown that state fatigue induced by sustained cognitive activity can be detrimental to subsequent endurance performance (Marcora et al, 2009). Therefore, state fatigue was quantified before each testing session using the fatigue scale of the Profile of Mood States (POMS-F) (Behrens et al, 2018). The POMS-F has been shown to provide a reliable and valid instrument to assess the level of state fatigue across a wide range of cohorts (O'Connor, 2004).…”
Section: State Fatiguementioning
confidence: 99%
“…Thus, some studies have also shown that motor performance is decreased when mental fatigue is induced [ 8 , 13 , 14 , 15 , 16 ]. For example, Behrens et al (2018) observed increased gait variability, assessed by the coefficient of variation of speed, stride length, and stance time after mental fatigue in older adults [ 17 ]. As increased gait variability has been described as a fall-risk predictor, the authors concluded that mental fatigue could be an intrinsic risk factor for accidental falls [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Behrens et al (2018) observed increased gait variability, assessed by the coefficient of variation of speed, stride length, and stance time after mental fatigue in older adults [ 17 ]. As increased gait variability has been described as a fall-risk predictor, the authors concluded that mental fatigue could be an intrinsic risk factor for accidental falls [ 17 ]. Additionally, it has been reported that mental fatigue led to an increased likelihood of slip initiation, poorer slip detection, and a more inefficient reactive recovery response to laboratory-induced slip-like perturbations in young adults [ 18 ], further suggesting that mental fatigue could be a risk factor for falls.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, participants’ responses to the usability part of the questionnaire indicated an overall confidence that our setup is effective in investigating manifestations of disorientation among cognitively healthy older adults and people with dementia. Furthermore, the first patient with dementia sampled experienced fatigue while navigating the route (akin to the finding of Behrens et al [ 27 ]), which suggests that dual-task conditions can be mentally exhausting among older participants. Therefore, this effect could be exacerbated by the increased difficulty of multitasking as a result of cognitive deficits [ 45 ].…”
Section: Discussionmentioning
confidence: 68%
“…Gait kinematics and kinetics, as well as spatio-temporal gait parameters, can be derived from the motion capturing data [ 23 ]. The system has been used, for example, for rehabilitation exercise [ 24 ] or for gait analysis in different settings [ 25 - 27 ].…”
Section: Methodsmentioning
confidence: 99%